1986
DOI: 10.1099/00207713-36-3-422
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus canis sp. nov.: A Species of Group G Streptococci from Animals

Abstract: f3-Hemolytic group G streptococci from cows with mastitis and from dogs with different pathological conditions were characterized and named Streptococcus canis sp. nov. These animal group G strains were differentiated from Streptococcus dysgalactiae (group G strains of human origin, as well as group L strains and certain animal and human group C strains) by simple physiological and biochemical tests. Deoxyribonucleic acid-deoxyribonucleic acid hybridization showed that the S . canis strains differed from S . d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
84
3
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(97 citation statements)
references
References 17 publications
9
84
3
1
Order By: Relevance
“…Our results are lower than the observations of Lammler et al (1987), Vieira and Castro (1994) and Facklam (2002), who reported CAMP-like reaction in 74.1%, 100% and 95% of strains, respectively. On the contrary, other studies have reported the absence of CAMP-like reactions (Clark et al 1984;Devriese et al 1986). …”
Section: Resultsmentioning
confidence: 46%
See 3 more Smart Citations
“…Our results are lower than the observations of Lammler et al (1987), Vieira and Castro (1994) and Facklam (2002), who reported CAMP-like reaction in 74.1%, 100% and 95% of strains, respectively. On the contrary, other studies have reported the absence of CAMP-like reactions (Clark et al 1984;Devriese et al 1986). …”
Section: Resultsmentioning
confidence: 46%
“…There was one prevalent biotype among the isolated strains which produced phosphatase, leucine amidopeptidase, arginine dihydrolase, alpha-D-and beta-D-galactosidase and fermented lactose and ribose. Results from the biochemical tests that are typically variable (including pyrrolidonylarylamidase, alpha-D-and beta-D-galactosidase, beta-D-glucuronidase, and acidification of lactose and trehalose) were generally within the range of proportions reported for S. canis by other researchers (Clark et al 1984;Devriese et al 1986;Efstratiou et al 1994;Vieira and Castro 1994;Soedarmanto and Lammler 1996). Only 16.3% of S. canis strains were positive for esculin hydrolysis, which is in contrast to the results of Devriese et al (1986) and Vieira and Castro (1994), who found 100% and 90% of strains positive, respectively.…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…Although methicillin is not generally used in treatment of cows, MRSA is increasing in its significance as a cause of bovine mastitis (Bernabé et al, 2005;Turutoglu et al, 2006). Acquisition of MRSA may occur through direct contact with humans: one outbreak of mastitis has been attributed to contact with a farm worker (Devriese et al, 1986), and more recent empirical evidence concurs with this (Fox et al, 1991;Roberson et al, 1994). However, this is slightly contentious as evidence to the contrary suggests that transmission between humans and cows is rare (Kapur et al, 1995;Lopes et al, 1990) due to the host-specificity of S. aureus clones (Smith et al, 2005).…”
Section: Cattle Associated Mrsamentioning
confidence: 87%